High-flux sublimation of a 3D carbon/carbon composite: Surface roughness patterns. (March 2021) - Levet, Cyril; Lachaud, Jean; Ducamp, Virginie; Memes, Régis; Couzi, Jacques; Mathiaud, Julien; Gillard, Adrien P.; Weisbecker, P.; Vignoles, Gérard L.
Abstract: 3D carbon-fibre reinforced carbon composites (3D C f / C ) are used as thermal protection systems for atmospheric re-entry, where they are exposed to strong ablation. Particularly, sublimation of the carbonaceous material plays an important role during the re entry. To study this, an arc image furnace under controlled Argon flow is used, with heat fluxes of 8 MWm −2 to 10 MWm −2 . The furnace and the sample thermal response have been numerically simulated prior to the experiments and match in-situ temperature measurements. Scanning electron microscopy and 3D profilometry with digital optical microscopy were used in order to characterise the epi-macro-structural and the epi-micro-structural roughness of the composite surface, evidencing a faster recession of the fibres as compared to the matrix. Carbon nanotextures have been assessed by using High-Resolution Transmission Electron Microscopy and Polarised Light Optical Microscopy, showing that the matrix is more organised than the fibre. This can explain the "inverse" behaviour under sublimation as compared to oxidation. The results have been qualitatively interpreted using numerical simulation of differential surface recession. Graphical abstract: Image 1 Highlights: 3D C f / C composites were submitted to fluxes of 8-10 MWm −2 in 1-10 kPa Ar in an image furnace. The surfaces were investigated by SEM and show a very specific roughness morphology. The fibre recedes faster than the matrix, as opposed to oxidation tests. Diffusion of sublimation products is not a limiting phenomenon. Modeling confirms experimental findings. The degree of organization of the carbon-based constituents has a positive impact on the recession rate.